BMPER alleviates ischemic brain injury by protecting neurons and inhibiting neuroinflammation via Smad3‐Akt‐Nrf2 pathway. (14th December 2021) - Ding, Peng; Chen, Wei; Yan, Xiaodi; Zhang, Jinxiang; Li, Cheng; Zhang, Guangming; Wang, Yongqiang; Li, Yonghua
Abstract: Aims: Bone morphogenetic proteins (BMPs) are a group of proteins related to bone morphogenesis. BMP‐binding endothelial regulator (BMPER), a secreted protein that interacts with BMPs, is known to be involved in ischemic injuries. Here, we explored the effects of BMPER on cerebral ischemia and its mechanism of action. Methods: A mouse model of brain ischemia was induced by middle cerebral artery occlusion (MCAO). An in vitro ischemic model was established by subjecting primary cultured neurons to oxygen‐glucose deprivation/reperfusion (OGD/R). Serum levels of BMPs/BMPER were measured in MCAO mice and in patients with acute ischemic stroke (AIS). Brain damages were compared between BMPER‐ and vehicle‐treated mice. Quantitative polymerase chain reaction (qPCR), immunohistochemistry, and immunofluorescence staining were performed to examine neuroinflammation and cell death. BMPER‐related pathways were assessed by Western blotting. Results: BMPER level was elevated in MCAO mice and AIS patients. BMPER administration reduced mortality, infarct size, brain edema, and neurological deficit after MCAO. Neuroinflammation and cell death after ischemia were alleviated by BMPER both in vivo and in vitro. BMPER activated the Smad3/Akt/Nrf2 pathway in OGD/R‐challenged neurons. Conclusion: BMPER is a neuroprotective hormone that alleviates ischemic brain injury via activating the Smad3/Akt/Nrf2 pathway. These findings may provide potential therapeutic strategies for stroke. Abstract : Terminal deoxynucleotidyl transferase dUTP nick‐end labeling (TUNEL) staining demonstrated that the number of dead/dying cells was pronouncedly increased in the brains of middle cerebral artery occlusion (MCAO) mice, which was attenuated by the bone morphogenetic protein‐binding endothelial regulator (BMPER) treatment.